PESANTREN SEBAGAI LEMBAGA PENDIDIKAN BERBASIS MASYARAKAT - Murdianto Murdianto; Muhammad Miki; Jalaluddin Jalaluddin (UIN Mataram, 2020)
Islamic boarding schools are informal educational institutions in Indonesia whose existence from the past until now is still in demand by the community. Public interest in pesantren is due to the fact that pesantren institutions are able to adapt to the progress of the world of education. Pesantren do not only focus on religious education materials, but also focus on general community-based materials, so that Islamic boarding schools are considered capable of fulfilling the needs of society in the modern era. In principle, Islamic boarding schools always make the community the basis of ideas or focus bases in determining learning strategies and educational materials. In this study, the authors focus on how Islamic boarding schools manage education based on community needs and the ability of pesantren to respond to contemporary studies.